Aslib Cranfield research project: report on the testing and analysis of an investigation into the comparative efficiency of indexing systems - Cleverdon, Cyril W. (Cranfield University, 1962)
This volume continues the account of the Aslib-Cranfield project as given in the "Final Report of the First Stage of an Investigation into the Comparative Efficiency of Indexing Systems". The major portion of the two years spent on this present stage has been involved with the analysis of the considerable amount of data which was obtained from the main test programme. A difficulty in this work was in deciding on the type of analysis which would be most likely to yield valuable information. In order to keep this volume within reasonable limits, it has been necessary to select from the analysis that was done, and even so in many cases only brief examples are given. The major emphasis has been placed on the reasons for failure to retrieve source documents, for this is considered to give some of the most interesting results of the project and has not, to our knowledge, been previously attempted. Of possible equal importance, but certainly more difficult to evaluate, is the reason for the retrieval of non-relevant references. This analysis has not been attempted within the present work, but will be one of the matters to be investigated in the continuation of the project.